Efektivitas Pupuk Kompos Limbah Broiler dengan Penambahan Tepung Tulang Ikan terhadap Pertumbuhan Rumput Setaria (Setaria sphacelata) : The Effectiveness of Compost Fertilizer from Broiler Manure with the Addition of Fishbone Flour on the Growth of Setaria Grass (Setaria sphacelata - Aprisasri Setyawan; Nuraeni; Soraya Faradila (Jurnal Agroekoteknologi dan Agribisnis, 2024)
The use of broiler manure as a single fertilizer does not provide optimal results due to its unbalanced nutritional content. Therefore, the supplementation of mineral sources ingredients such as fish bone meal are needed to improve the quality of broiler waste fertilizer. This study aims to determine the effectiveness of broiler waste compost fertilizer with the addition of fish bone meal on the productivity of Setaria sphacelata. The experimental design used complete randomized design consist of 4 treatments and 5 replications. The treatments were P0 = control (compost without fish bone meal), P1 = compost + 5 g fish bone meal/polybag, P2 = compost + 10 g fish meal/polybag and P3 = compost + 15 g fish meal/polybag. Parameters measured were plant height, number of leaves, wet weight and number of tillers. The data were analysis with Anova and Duncan Multiple Range Test. The results showed that the supplementation of fish bone meal had a significant effect on plant height, number of leaves, fresh weight and number of tillers of setaria grass (P<0.05). The higher the provision of fish bone meal in compost, the higher the growth of setaria grass. The P3 treatment (compost + 15 g fishmeal/polybag) was significantly higher than P0 and P1 while the P3 and P2 treatments were not significantly different. Supplementation of 15 g fish bone meal in compost increased the productivity of Setaria grass.